ANALYSIS OF THE EXISTING WAYS OF RECEIVING OF THE PISTON RINGS SLUGS PRODUCTION - A. N. Krutilin; A. I. Stanuk; D. I. Stanuk (Литьë и металлургия)
The analysis of existing ways of production of the piston ring slugs is carried out. The advantages and disadvantages of the ways are examined. The way of the slugs production is offered